1990
DOI: 10.1007/bf00117787
|View full text |Cite
|
Sign up to set email alerts
|

The identification of a neutral glycosphingolipid antigenic marker for metastatic cells in the R3230AC rat mammary adenocarcinoma

Abstract: The process of metastasis is a complex process involving numerous steps, and it is thought that cells able to complete all of these steps and form metastatic foci form a unique subpopulation of cells within the tumor. To study this metastatic subpopulation, a marker for the metastatic cells is required. We have previously described the enrichment of soybean agglutinin binding cells in tumor populations enriched for lymphatic metastasis [1]. In this study we provide evidence that the cell-surface structure bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Our laboratory has established a rat mammary tumor model where highly and poorly metastatic subpopulations, termed R3230Ac-LN 4 and R3230Ac-CAb, respectively, have been derived from the same R3230Ac rat mammary adenocarcinoma (21,30,32). In the experiments described in this paper, clonal isolates of these two cell populations, LN4D6 and CAbD5, were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory has established a rat mammary tumor model where highly and poorly metastatic subpopulations, termed R3230Ac-LN 4 and R3230Ac-CAb, respectively, have been derived from the same R3230Ac rat mammary adenocarcinoma (21,30,32). In the experiments described in this paper, clonal isolates of these two cell populations, LN4D6 and CAbD5, were used.…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory has established a rat mammary tumor model where highly (LN4D6) and poorly (CAbD5) metastatic subpopulations have been derived from the R3230Ac rat mammary adenocarcinoma (21). Stable LN4D6ϩpUB6-HA 3 CREB3L1 (LN4D6 CREB3L1) and LN4D6ϩpUB6-HA 3 vector-only (LN4D6 vector) transfected cell lines were generated.…”
Section: Methodsmentioning
confidence: 99%
“…Relevant in this respect are two recent reports by Carlsen et al which implicate a cell surface soybean agglutinin-binding glycolipid in lymphatic metastasis of a rat mammary adenocarcinoma. Depletion of cells bearing this glycolipid was shown to reduce significantly tumor cell potential to metastasize to the regional lymph nodes [39,40]. Its role in tumor cell adhesion has not, however, been elucidated.…”
Section: The Role Of Other Adhesion Moleculesmentioning
confidence: 99%
“…Of particular interest in this context are studies examining the range of gene expression in different cells in the population. Carlsen and coworkers [36,37] have demonstrated that the metastatic ability of rat mammary tumor cells is associated with the level of expression of a glycolipid on the cell surface that binds to soya-bean agglutinin (SBA). Thus, cell populations selected for high levels of SBA binding are more metastatic than cell populations with low levels of binding.…”
Section: Metastasismentioning
confidence: 99%
“…Thus, cell populations selected for high levels of SBA binding are more metastatic than cell populations with low levels of binding. Furthermore, these authors have recently shown [37] that deleting the cells with a high expression of the glycolipid using monoclonal antibody and complement-dependent cytolysis resuits in a reduction in the metastatic ability of the cell population.…”
Section: Metastasismentioning
confidence: 99%